(untitled) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2026)
This research aimed to identify the requirements for empowering Syrian women under the new administration from the perspective of faculty members at the Faculty of Education, Latakia University. The research sample consisted of 40 faculty members from the Faculty of Education. The descriptive method was used, and to achieve the research objective, a questionnaire was developed consisting of 30 items distributed across three dimensions: academic and cultural requirements, administrative requirements, and legal and legislative requirements. The results showed that the requirements for empowering Syrian women under the new administration, from the faculty members’ perspective, were considered to be at a high level. Legal and legislative requirements ranked first with a relative weight of 91.6%, followed by administrative requirements with a relative weight of 89.6%, and then academic requirements with a relative weight of 88.8%. The results also indicated a difference in faculty members’ opinions regarding the requirements for empowering Syrian women based on gender, with females showing higher levels of support. Differences were also found based on academic rank, with professors showing higher levels of support. However, no differences were found based on years of experience.